International legal regulation of protection and sustainable use of water courses - Vukasović Vid (Međunarodni Problemi)
The article deals with international legal regulation of protection and sustainable use of watercourses with special reference to the Sava River Basin. This regulation is considerably developed on universal, regional and sub regional international levels by a substantial number of declaratory treaty and other acts dealing with the subject. In case of the river Sava the basic frame for regulation is on the European level: the documents concerning the Danube River as a whole, and particularly the Framework Agreement on the Sava River Basin. The author stresses that adoption and ratification of this document is probably one of the biggest step forward in co-operation between Slovenia, Croatia, B&H, and Serbia and Montenegro.